Effectiveness of poultry based Farmers’ Producer Organization and its impact on livelihood enhancement of rural women - MUKHERJEE, ANIRBAN; SINGH, PREMLATA; RAKSHIT, SHANTANU; PRIYA, SATYA; BURMAN, RAJARSHI ROY; SHUBHA, KUMARI; SINHA, KANCHAN; NIKAM, VINAYAK (The Indian Journal of Animal Sciences, 2019)
Farmers Producer Company (FPC) has emerged as a new business model for the rural area. Like agriculture and horticulture, it is working in poultry sector too. With an intuition to find out the impact of poultry based Farmer Producer Company on upliftment of rural people, the present study was conducted by selecting Madhya Pradesh Women Poultry Producer Company Pvt. Limited (MPWPCL) founded by a team of poor rural women. An Ex-Post Facto research design was used. Difference in difference technique was utilized to estimate the actual impact of FPCs. To measure the effectiveness of MPWPCL and its impact, two indices, viz. effectiveness index and livelihood wellbeing index were prepared. Study was conducted in Orchha district of Madhya Pradesh from 37 randomly selected poultry growers’ members and 15 nonmember respondents from the same locale. The MPWPCL was found highly effective with overall effectiveness score of 71.88. Joining the FPC has improved the poor rural women’s human, social and political dimensions of livelihood empowerment in addition to a significant economic gain.